The Tragedy of Neonatal Sepsis in South Asia. Issue 1 (January 2023) - Callister, Lynn Clark
Abstract : The rate of neonatal mortality due to infection in South Asia is alarming. India is ranked highest in the world for neonatal deaths, with 5 million babies dying in 2019 per the World Health Organization. Nigeria, Pakistan, Ethiopia, and the Democratic Republic of Congo collectively account for almost 50% of neonatal deaths world-wide. Our global health and nursing expert, Dr. Callister, discusses this problem and what is being done to improve care.